2005
DOI: 10.2463/mrms.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging of the Liver: Technical Challenges and Prospects for the Future

Abstract: DiŠusion-weighted imaging (DWI) has recently been attempted in the abdominal region. We review diŠusion-weighted images of the liver, especially from the technical point of view. We discuss selection of pulse sequence parameters, eŠects of anti-breathing motion technique, tips for measuring apparent diŠusion coe‹cient (ADC), and utility of superparamagnetic iron oxide (SPIO), showing clinical cases, including those at 3T. Our current trial of new pulse sequencing, such as SPIO-mediated breath-holding black-blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
4

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 38 publications
2
137
0
4
Order By: Relevance
“…If the fat suppression technique was diŠerent from our methods or superparamagnetic iron oxide was used simultaneously, the results obtained might be changed from those of this paper. 17 Furthermore, respiratory triggering itself was not the ideal solution to compensate for the respiratory motion of the liver. The result of this paper also revealed that three of 30 patients showed respiratory misregistration even in RT-DWI.…”
Section: Discussionmentioning
confidence: 99%
“…If the fat suppression technique was diŠerent from our methods or superparamagnetic iron oxide was used simultaneously, the results obtained might be changed from those of this paper. 17 Furthermore, respiratory triggering itself was not the ideal solution to compensate for the respiratory motion of the liver. The result of this paper also revealed that three of 30 patients showed respiratory misregistration even in RT-DWI.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted magnetic resonance (MR) imaging (DWI) offers high lesion-to-background contrast and allows quantifying diffusion by means of apparent diffusion coefficient (ADC) measurements, making it a valuable technique for the detection and characterization of liver lesions [1,2], and characterization of the liver parenchyma itself [3,4]. However, signal loss in DWI and artificially elevated ADCs have been reported to occur in the left liver lobe [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have made it feasible to apply diffusion MRI techniques for abdominal imaging. 36 In hepatic fibrosis, it is thought that collagen is not rich in free unbound water. Thus, the accumulation of fibrosis causes a reduction in the amount of water proton diffusion in affected liver tissue.…”
Section: Novel Mr Applications For In Vivo Detection Of Hepatic Fibrosismentioning
confidence: 99%
“…Thus, the accumulation of fibrosis causes a reduction in the amount of water proton diffusion in affected liver tissue. 36,37 Recent advances in MRI technology have facilitated the performance of diffusion-weighted MRI of the liver. Previous experience with physiological motion artifacts and poor image resolution have been addressed by the use of faster pulse sequences, cardiac and respiratory triggering, and modifying the acquisition to allow data collection during suspended respiration.…”
Section: Novel Mr Applications For In Vivo Detection Of Hepatic Fibrosismentioning
confidence: 99%